Translation of cultural-specific Phrases of Kachach’s Novel: The American Granddaughter - Falah Hussein Hanoon Al-Sari ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study explores the translation of Inaam Kachachi’s novel The American Granddaughter, a poignant exploration of identity and memory during the aftermath of the Iraqi war. This novel was originally written in Arabic, under the title الحفيدة الأمريكية, in 2008. It has been translated into English by Nariman Youssef in 2010. This study shows how Youssef employs various translation approaches and techniques to successfully transfer the cultural complexity and literary style of the source text into English. By analyzing the accuracy of the translation of the culturally specific terms and expressions in the source text, this study investigates whether the translated text succeeded in capturing the novel’s cultural context without much loss.